The Dynamics of Self-Regulated Learning of Students from Rural Area: Study on the Impact of Ecological Changes - Jaha, Dortean Amelia Jois ; Rajagukguk, Christin Prima Mery; Lumba, Anderias J. F.; Ate, Christmas Prasetia (Universitas Nusa Cendana, 2025)
This study examines the Self-Regulated Learning (SRL) of Wewewa students from Southwest Sumba, who are studying in Kupang, focusing on their adaptation to ecological changes. Using a mixed-methods approach, it combines qualitative phenomenological analysis and quantitative Likert scale surveys. Results show that most students prefer studying at night due to a quieter atmosphere and cooler temperatures. As many as 80% have at least intermediate-level technological skills, which facilitates access to digital learning resources. The dominant stress management strategies are exercise (65%), meditation (25%), and social support (10%). Findings indicate that urban ecological factors influence students' SRL and academic adaptation. This study highlights the need for institutional support programs to help rural students adapt to urban environments and provides insights into the relationship between environmental changes, learning strategies, and students' psychological well-being.